Penerapan Konsep Green Architecture dalam Perancangan Hotel Resort di Kabupaten Tasikmalaya - Candra Sapta Permana; Asep Yudi Permana; Nitih Indra Komala Dewi (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2020)
To develop Indonesia's tourism industry, the government of the Republic of Indonesia has made the tourism industry a leading sector that can help boost Indonesia's economy. The government, especially West Java Province, focuses on developing the tourism industry in West Java by making big plans for world-class tourist destinations in West Java Province. To support this plan, it is necessary to get good facilities and infrastructure, one of which is accommodation facilities (resort hotels) which become a place for domestic or foreign tourists to stay. An increase in the number of tourists staying in West Java was 6.95% in 2016 and 2017, so it must be accompanied by an increase in the number of lodging accommodation The aim and purpose of the design of the Green Hotel Resort are to accommodate the increasing number of tourists who will stay in West Java and at the same time supporting the West Java Provincial Government's plans to create friendly tourist destinations. So that the theme of designing Green Hotel Resort is green architecture, which is expected to reduce environmental damage due to tourism and accommodation, due to the increase in the number of tourists to West Java Province. The design produced in this design is a hotel resort design that can maximize the potential in the site, that it can reduce energy use in buildings. This hotel resort not only functions as an accommodation facility, but is also equipped with a vehicle for educational tours of the craft and the unique culture of Tasikmalaya.